The BCR-ABL1 Inhibitors Imatinib and Ponatinib Decrease Plasma Cholesterol and Atherosclerosis, and Nilotinib and Ponatinib Activate Coagulation in a Translational Mouse Model - Pouwer, Marianne G.; Pieterman, Elsbet J.; Verschuren, Lars; Caspers, Martien P. M.; Kluft, Cornelis; Garcia, Ricardo A.; Aman, Jurjan; Jukema, J. Wouter; Princen, Hans M. G. (Frontiers in Cardiovascular Medicine, 2018)
Treatment with the second and third generation BCR-ABL1 tyrosine kinase inhibitors (TKIs) increases cardiovascular risk in chronic myeloid leukemia (CML) patients. We investigated the vascular adverse effects of three generations of TKIs in a translational model for atherosclerosis, the APOE*3Leiden.CETP mouse. Mice were treated for sixteen weeks with imatinib (150 mg/kg BID), nilotinib (10 and 30 mg/kg QD) or ponatinib (3 and 10 mg/kg QD), giving similar drug exposures as in CML-patients. Cardiovascular risk factors were analyzed longitudinally, and histopathological analysis of atherosclerosis and transcriptome analysis of the liver was performed. Imatinib and ponatinib decreased plasma cholesterol (imatinib, -69%, P<0.001; ponatinib 3mg/kg, -37%, P<0.001; ponatinib 10 mg/kg -44%, P<0.001) and atherosclerotic lesion area (imatinib, -78%, P<0.001; ponatinib 3 mg/kg, -52%, P=0.002; ponatinib 10 mg/kg, -48%, P=0.006), which were not affected by nilotinib. In addition, imatinib increased plaque stability. Gene expression and pathway analysis demonstrated that ponatinib enhanced the mRNA expression of coagulation factors of both the contact activation (intrinsic) and tissue factor (extrinsic) pathways. In line with this, ponatinib enhanced plasma levels of factor VII, whereas nilotinib increased plasma FVIIa activity. While imatinib showed a beneficial cardiovascular risk profile, nilotinib and ponatinib increased the cardiovascular risk through induction of a pro-thrombotic state.